Complications and Outcome of Primary Intracerebral Hemorrhage at a Tertiary Care Hospital in Bangladesh: A Follow Up Study (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Patient admitted with hemorrhagic stroke, particularly primary intracerebral hemorrhage (ICH) may develop different form of complications during their hospital stay.Objective: The objectives of the study were to find out the different complications of primary intracerebral hemorrhage among admitted patient and their effect on hospital stay and outcome.Methodology: This was a hospital based observational follow up study conducted at National Institute of Neurosciences and Hospital, Dhaka, Bangladesh in a period of 18 months (from February 2021 to August 2022). Total 570 (504 finally analyzed) primary intracerebral hemorrhage patient who admitted within 48 hours of onset of stroke were enrolled consecutively by purposive sampling method. Routine biochemical, hematological tests and computed tomography scan were done to all participants. All patients were followed up every day during hospital stay and any complication developed were noted. Patients’ outcome (discharge / death) was recorded.Results: This study revealed that mean (SD) age of participants were 59.1 (±13.4) years with majority male 262(52.0%). Electrolyte imbalance (hyponatremia) was the commonest complication found in 212 (42.1%) of patient followed by hematoma expansion 22.6%, hydrocephalus 15.5%, aspiration pneumonia 11.1%, convulsive seizure 10.0%, urinary tract infection and pressure sore both are 3.6%. Deep vein thrombosis was found in1.2%. Hypertension was the commonest risk factor (93.0%) followed by Diabetes mellitus (28.1%). Older (>50 years) age (OR: 0.53; 95% CI: 0.36-0.80; p = 0.002), urban dwellers (OR: 1.56; 95% CI: 1.04-2.27; p =0.013) and poor (